From comb-like polyelectrolytes to polyelectrolyte-surfactant complexes: Effect of the length of the aliphatic tail of the counterions on self-organization in solid state. (5th June 2021) - Fetin, P.A.; Brevnov, O.N.; Kadnikov, M.V.; Fetina, V.I.; Bilibin, A. Yu.; Zorin, I.M.
Graphical abstract: Highlights: Polyelectrolyte complexes of comb-like polyelectrolyte were investigated. Hexagonal packing transformation to amorphous and then lamellar packing observed. The ordering is confirmed by small-angle X-ray diffraction. Formed structures are stable up to 150 °C then chemical decomposition take place. The mechanism of complexes thermal decomposition is proposal. Abstract: Cationic comb-like polyelectrolyte poly(11-acryloyloxyundecyltrimethylammonium) with acidic residues of acetic, butanoic, hexanoic, octanoic, decanoic, dodecanoic acids as counterions were synthesized. Those polyelectrolyte series on increasing of counterion tail length demonstrate the smooth transition from typical comb-like polyelectrolytes to polyelectrolyte-surfactant complexes. All complexes are water soluble, and dissociate in aqueous NaCl. Increasing of counterion hydrophobicity results transformation from hexagonal packing (acetic and butanoic counterions) to amorphous phase (hexanoic counterions) and then to lamellar packing (octanoic, decanoic and dodecanoic counterions) of solid complexes. The formed structures are stable up to 150 °C and decompose with destruction of chemical structure.